Vergleichende chemische, biologische und klinische Untersuchungen von 99mTc-DMS und 99mTc-GH zur Verwendung für die Nierenszintigraphie - Vanlić-Razumenić, N.; Malešević, M.; Stefanović, Lj. (Nuklearmedizin - NuclearMedicine, 1979)
The renal radiopharmaceutical preparations 99mTc-DMS and 99mTc-GH were examined chemically, biologically and clinically. Both preparations are of high radiochemical purity. The biodistribution of both preparations was examined in experimental animals at different time intervals, from 15 min to 4 hr; the percentage of incorporation of 99mTc-DMS into kidneys is much higher (29.4% to 52.0%) than that of 99mTc-GH (12.80% to 22.20%). Both preparations accumulate to a greater extent in the renal cortex than in the medulla.The most suitable time for renal scintigraphy for "mTc-DMS is 90-150 min while for 99mTc-GH it is 60-90 min. It is concluded that 99mTc-DMS is more suitable for static scintigrams on the scanner and 99mTc-GH for dynamic studies with the gamma camera.